EDUCATIONAL AND UPBRINGING PRACTICES IN L. MONTGOMERY’S WORKS AND THEIR RELEVANCE IN TODAY’S EDUCATION SYSTEM (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This paper explores the educational and upbringing practices reflected in the literary works of Lucy Maud Montgomery, particularly focusing on her portrayal of child development, character formation, and moral values. The study highlights how Montgomery’s narratives, notably in Anne of Green Gables and its sequels, offer timeless pedagogical insights. Through her characters’ interactions and community-based learning, the works emphasize empathy, creativity, responsibility, and the importance of emotional intelligence. The article argues that Montgomery’s educational ideals align with many modern principles in today’s learner-centered and values-based educational systems, making her literature both relevant and instructive in contemporary pedagogical contexts.